If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 2) = 7 Reorder the terms: 2(2 + y) = 7 (2 * 2 + y * 2) = 7 (4 + 2y) = 7 Solving 4 + 2y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2y = 7 + -4 Combine like terms: 4 + -4 = 0 0 + 2y = 7 + -4 2y = 7 + -4 Combine like terms: 7 + -4 = 3 2y = 3 Divide each side by '2'. y = 1.5 Simplifying y = 1.5
| p-7=7 | | (2y-91)/2y=1/14 | | 2*14=21 | | 9v+17=-6 | | r/2-39=41 | | 2k-9=-15 | | 0.005439x^2-0.37x=0 | | 1/2(t+4)=13 | | 1+6lnx=0 | | 17x+12=8x | | x^2+12x+33=1 | | 7-4p=2p-5 | | f(1)=x^2+12x+33 | | f(x)=x^2+12x+33 | | -m/42=5 | | S=4nr+2nrh | | S=4nr+2nr | | (9+x)(x-6)=0 | | 2=10+7/-3 | | 5x+1=10+x | | 14r^2-23r+8=0 | | 32+4s-s^2=0 | | 2a^2-13ab+20b^2=0 | | 9x-12y+9=19x-15y+10 | | 39-9n=-6n | | (16X+9Y-7Z)+(-8X-5Y)= | | 3g-8=fg-20 | | Y=13-9x | | 2e^2x-1=5 | | 4x+5y=38 | | 8-4d-6d-8=2d | | 4cos(x)-5sin(x)=3 |